Synthesis and Characterization of Conjugated Polymers Based on Benzoselenadiazole - Sun, Xiaoxia; Lei, Xiaolong; Hu, Yu (Asian Journal of Chemistry, 2015)
A multistep synthesis of the electron-poor 4,7-di(thiophen-2-yl)benzo[c][1,2,5]selenadiazole are presented. The new deficient acceptor has good solubility in organic solvents to permit an appropriate coating process. P1 was synthesized by direct oxidative polymerization under the reaction condition with FeCl3 and CH3NO2. The spectra of polymers P1 to P2 show homogenous absorptions across most of the visible spectrum (450-650 nm). Solutions of P1 show a dark purple-black colour due to the lack of absorption in the far blue and red regions. And the solution of P2 exhibits a bright orange-red colour due to the increased reflection/transmission of red light. Both of the polymers were characterized by IR, UV-visible and cyclic voltammetry.